Implementation of a culture of comprehensive self-evaluation in the Facultad de Odontología, Universidad de Antioquia: retrospective from 1993 to 2023* - Yepes-Delgado, Fanny Lucía; Acevedo-Gil, Diana Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: Since 1993, the Facultad de Odontología, Universidad de Antioquia, has been continuously and comprehensively developing self-assessment processes aimed at ensuring the academic quality of the program. This study aimed to identify the impact that this process has had on the implementation of a culture of self-assessment and improvement. Methods: A qualitative approach that corresponds to a case study, which incorporates some ethnographic techniques was conducted. The study consisted of four phases: diagnosis of how the academic community conceives self-assessment, description of the main results of these processes, historical review between 1993-2023, and the proposal of a tool for information management. It also included the application of a survey applied to 40 representatives of the academic community. After categorization, triangulation and analysis of the data, different ways of perceiving the process were identified, the results were validated and socialized. Results: Self-assessment is done with objectives such as academic process evaluation, qualified registration, opening of a cohort for postgraduate studies and high-quality accreditation, but are often conceived as an administrative requirement. The decentralization of information and inconsistency in data generates trauma. Continuous academic improvement is recognized as a product of these exercises. Conclusions: The trajectory of the Faculty of Dentistry in strengthening a culture of self-assessment has generated changes in the attitudes and habits of its members by shifting the focus from the process as a norm to assuming it as a reflective and participatory exercise that guides the achievement of program quality objectives. The need is emphasized to continue articulating validity and reliability in the process, through continuity in the reflection-action-registration cycle and systematic tracking of information and actions.